Recognizing Modal Versions of Tonality by Students of Preschool and Early Childhood Education - Ewa Anna Zwolińska; Paweł Trzos (Edukacja Elementarna w Teorii i Praktyce)
The vast majority of preschool and early childhood teachers admit that they have problems with implementing musical issues. Experimental research indicates that the inability to sing, move to music, differentiate tonality and meter, improvise, read and write down music, is mainly caused by deficits in audiation. The article focuses on research results regarding the effectiveness of recognizing a melody presented instrumentally in eight tonalities: 1. Major; 2. Dorian; 3. Phrygian; 4. Lydian; 5. Mixolydian; 6. Aeolian; 7. Harmonic Minor; 8. Locrian. Due to the purpose of the research, the rhythmic content of all versions was the same, and the procedure used allowed for comparing students’ attention by determining the time of receiving (listening to) the melodic line and the moment at which they gave the answer. Listening skills help develop critical thinking skills, which are important in any form of communication: speaking, singing, reading, writing or synthesizing information.